Предмет: Математика,
автор: Oksanka20032209
найдите корень уравнения 5,6-3(2-0,4х)=0,4(4х+1)
Ответы
Автор ответа:
0
5,6-6+1,2х=1,6х+0,4
0,4х=-0,8
х=-2
0,4х=-0,8
х=-2
Автор ответа:
0
Раскроем скобки:
5,6 - 6 + 1,2х = 1,6х + 0,4
1,2х - 1,6х = 0,4 - 5,6 + 6
-0,4х = 0,8
х = 0,8 : (-0,4)
х = - 2
Проверка: 5,6 - 3(2 - 0,4 *(-2)) = 0,4(4 * (-2) + 1)
5,6 - 3(2 + 0,8) = 0,4(-8 + 1)
5,6 - 3 * 2,8 = 0,4 * (-7)
5,6 - 8,4 = - 2,8
- 2,8 = - 2,8
5,6 - 6 + 1,2х = 1,6х + 0,4
1,2х - 1,6х = 0,4 - 5,6 + 6
-0,4х = 0,8
х = 0,8 : (-0,4)
х = - 2
Проверка: 5,6 - 3(2 - 0,4 *(-2)) = 0,4(4 * (-2) + 1)
5,6 - 3(2 + 0,8) = 0,4(-8 + 1)
5,6 - 3 * 2,8 = 0,4 * (-7)
5,6 - 8,4 = - 2,8
- 2,8 = - 2,8
Похожие вопросы
Предмет: Другие предметы,
автор: milanamavlyukova
Предмет: Окружающий мир,
автор: Аноним
Предмет: Информатика,
автор: seak279999
Предмет: Биология,
автор: sultanmirzaev